Central Bank independence: The case of North African Central Banks - Amina Haoudi; Ali Bennagem Touati (Journal of Central Banking Theory and Practice, 2023)
The independence of Central Banks is still considered tobe a credibility factor in ensuring price stability. Thus, many centralbanks in transition countries have undergone a change in their stat-utes in order to achieve greater independence from governments. Inthis vein, within a decade, North African Central Banks have put inplace a new institutional framework for their monetary policy. Inthis article, we will attempt to assess and measure the legal (de jure)and real (de facto) independence of these Central Banks (Morocco,Algeria, Libya, Tunisia, Egypt).
Keywords: E42; E58; 330; Central Bank Independence; monetary policy; NorthAfrica